The Probe Team [episode no. 283] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
A leadership crisis within the majority on the accusations of graft and corruption, ranging from scandalous merienda spending, to questionable purchases of memorial plans is presented in Crisis in Congress. An in terview with some faculty and students of the University of the Philippines, in particular in shown in Sexual Harassment on campus. Books from the heart is about Nancy and Dan Harrington bridging the gap of lack for books and learning materials in Philippine public schools.
A Crisis in the Congress (20 min.) -- Sexual Harassment on Campus (15 min.) -- Books from the Heart (15 min.)
Reporting, Cheche Lazaro and Marga Ortegas.
Keywords: Sexual harassment in universities and colleges; Gift books -- Philippines; Philippines. Congress -- Officials and employees